Unconfined compressive strength and pore structure evolution law of structural clay after disturbance - Tang, Bin; Xie, Liang; Wang, Wei; Zhou, Biaohe; Gong, Yanxia (Frontiers in Earth Science, 2022)
The clay in the Zhanjiang Formation has thixotropic property, which has great influence on the foundation engineering in Zhanjiang area. The evolution law of macroscopic strength and microstructure of clay during thixotropy can be used to explain the practical engineering problems caused by thixotropy. For undisturbed soil and reconstituted soil curing for different time, unconfined compressive strength test, scanning electron microscopy and mercury injection porosimetry test were carried out to obtain the unconfined compressive strength and pore structure evolution law in the thixotropic process. The results show that: the Zhanjiang Formation structural clay is very sensitive to disturbance, and the unconfined compressive strength of the clay decreases from 180.29 kPa to 11.73 kPa after the natural structure is completely destructed. After 300 days of curing, the unconfined compressive strength of clay increased from 11.73 kPa to 53.43 kPa due to thixotropy, which increased by 3.55 times. The stacking flaky flocculation structure of the undisturbed soil is destructed by reconstituting, turning to flaky flocculation structure, and the large pores are homogenized, and the small pores develop into medium pores, and the decrease of soil strength. In the process of thixotropy, the soil particles gradually coagulate and form an aggregates flocculation structure, and the strength of clay increases with the increase of the degree of cementation. Based on the results, the thixotropic pattern of clay was established and its thixotropic mechanism was explained.